2022
DOI: 10.1136/rapm-2022-103823
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role for regional analgesia in children with spina bifida: a retrospective observational study comparing the efficacy of regional versus systemic analgesia protocols following major urological surgery

Abstract: IntroductionRegional techniques are a key component of multimodal analgesia and help decrease opioid use perioperatively, but some techniques may not be suitable for all patients, such as those with spina bifida. We hypothesized peripheral regional catheters would reduce postoperative opioid use compared with no regional analgesia without increasing pain scores in pediatric patients with spina bifida undergoing major urological surgery.MethodsA retrospective review of a multicenter database established for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A study of children with VP shunts undergoing augmentation cystoplasty using bowel found no difference in the rate of shunt infections between those who did and did not undergo bowel preparation (34). Similarly, there were no VP shunt infections following introduction of an ERAS protocol for pediatric urinary tract reconstruction that included elimination of a dedicated, preoperative bowel preparation and maintenance of routine outpatient bowel regimens in those with concomitant neurogenic bowel (10). This particular example illustrates the consideration in outcomes among different patient populations when evaluating whether intended effects of ERAS elements are equally distributed.…”
Section: Elimination Of Mechanical Bowel Preparationmentioning
confidence: 91%
See 4 more Smart Citations
“…A study of children with VP shunts undergoing augmentation cystoplasty using bowel found no difference in the rate of shunt infections between those who did and did not undergo bowel preparation (34). Similarly, there were no VP shunt infections following introduction of an ERAS protocol for pediatric urinary tract reconstruction that included elimination of a dedicated, preoperative bowel preparation and maintenance of routine outpatient bowel regimens in those with concomitant neurogenic bowel (10). This particular example illustrates the consideration in outcomes among different patient populations when evaluating whether intended effects of ERAS elements are equally distributed.…”
Section: Elimination Of Mechanical Bowel Preparationmentioning
confidence: 91%
“…Thus, achieving intraoperative euvolemia with the goal of maintaining adequate renal perfusion is of the utmost importance (40). This tenet is reflected in the ubiquitous adoption of minimizing excessive intraoperative fluids in both pediatric colorectal surgery and pediatric urology (4,7,10,41,42).…”
Section: Maintenance Of Euvolemiamentioning
confidence: 99%
See 3 more Smart Citations